(untitled) (Global Journal of Management and Business Research, 2015)
Grameen Bank (GB) is a micro lending organization in Bangladesh that was initiated by Professor Muhammed Yunus as a pilot project in Jobra village in 1976. It provides small loans to rural poor women, without collateral, following group lending peer support methodologies. It disburses 16.7 billion to 8.67 million borrowers through 2247 branches across Bangladesh. The loan repayment rate is 97%. It is a self-sufficient financial institution. GB’s unique program implementation steps make it successful in achieving its goals of creating self-employment and creates choice among rural poor women; thereby increasing their income, empowering them, and promoting environmentalism in rural Bangladesh.